Smart Environment Program’s Traffic Management to Achieve Semarang City Resilience - Armawi, Armaidy; Danugroho, Agus; Apriliyanti, Kiki; Asrofi, Akhmad (Universitas Muhammadiyah Yogyakarta, 2022)
This research aims to study how the Semarang City Smart Environment-based traffic management during the Covid-19 Pandemic. The pandemic condition that affected all sectors, including traffic management, is a critical issue to study. In addition, based on the analysis of the VOSViewer software, research on the Smart Environment program-based traffic management during a plague is still not much research. This research is a descriptive qualitative study assisted by the data analysis software NVIVO 12 Plus. Data were collected from several related agencies and also supported secondary data. The results of this study indicate that the traffic management strategy through the Smart Environment during the COVID-19 Pandemic is a form of inter-agency integration in its implementation regulated in the Government Regulation on the Traffic and Road Transport Forum. The regulation realization takes place vertically and horizontally. The Smart Environment implemented traffic governance to overcome traffic problems is by utilizing the coordination of ATCS with the Semarang City Police Department and providing opportunities for the community to carry out complaints through Lapor Hendi and Call Center 112. The traffic governance affected three Gatra, namely economic, socio-cultural, and defense and security. Thus, it helps to support Semarang City to achieve its resilience.